A critical review of the response of the Environmental Literacy Skills Programme to learner capabilities, and to the demands of the Working for Water training setting in an emerging Green Economy - Fourie, Kathryn (Rhodes University, Faculty of Education, Department of Education, 2017)
This case study is guided by a social realist research approach. It is an investigation into if and how the Environmental Literacy Skills Programme (ESLP) responds to Working for Water learners' capabilities and the enabling and constraining factors that shape these, and to the demands of the WfW training setting in an emerging Green Economy. The context for the study is that of the Working for Water programme, an Expanded Public Works Programme (EPWP) run under the auspices of the Department of Environmental Affairs in South Africa. The study took place while piloting the newly created ELSP materials with a group of beneficiaries and contractors in Uitenhage, a town in South Africa's Eastern Cape Province. The study provides insights into the application of accredited training in an EPWP training environment, and critically considers the academic and practical suitability of the ELSP in the WfW context. It achieves this by considering how the ELSP seeks to respond to the education levels and experiences of contractors and beneficiaries, and the demands of the WfW training setting. To understand what underpins learner capabilities and experiences, it was necessary to investigate the conversion factors and enabling and constraining factors that influence WfW contractor and beneficiary capabilities and involvement in the ELSP training in the context of an emerging Green Economy. To develop these insights, data was gathered through participant observation, questionnaires, structured and semi-structured interviews, as well as document analysis. The theoretical framework of Amartya Sen's (1999) Capability Approach supports the study, which provides an alternative way of understanding the freedoms that people enjoy, or the lack of freedom they experience, in being able to live the kind of life they have reason to value. The Capability Approach provides the key concept of resource conversion, which is used in the study to discern the social, personal and environmental constraints and enablers that people experience in their lives. These either assist or dis-enable a person in converting a resource such as education, into a functioning such as desired employment. Through a social realist causal analysis model, key structures are identified that underpin the actions of beneficiaries and contractors in relation to their learning and career pathways. The study shows that while the ELSP does support the development of green skills and in part responds to learner capabilities (and enabling and constraining conversion factors), there is a lack of information as to where those skills can be applied in elementary green occupations, in part due to South Africa's focus on high-skills development linked to Green Economy objectives. The study makes recommendations for aligning environmental education with career guidance, as well as a recommendation for further detailed research into identifying elementary green occupations and associated learning pathways.
Keywords: Working for Water Programme; Environmental Literacy Skills Programme; Environmental education -- South Africa